As competências do gestor escolar: um estudo realizado na coordenação regional de Luziânia – (GO) - Siqueira, André Bonifácio (2023)
The educational organization, like other entities and organizations, is part of this globalized and connected world, full of changes, with trends that require articulated action, a vision of the whole and the future, the ability to plan, understand, execute and control. This contingency environment generates high impacts on administrative problems, which are uncertain and complex; This makes it clear that, to understand and adapt to so many transformations, it is necessary for the school manager to have character and personality, but also knowledge, skills and abilities. Thus, the research objective of this dissertation is to present the skills of the school manager with a contingency focus in the administrative scope of schools linked to the Regional Education Coordination of Luziânia. To this end, it is proposed to carry out applied, qualitative, exploratory and descriptive research. In this research, all managers-directors of schools with basic education participated, in the urban area of the municipality of Luziânia – Goiás (GO), totaling 19, with full-time and military schools not being the subject of this research. As for the procedure, the research was bibliographic with general characteristics based on material already prepared, while, to get to know the research participants, the procedure was field research. The instruments for data collection were bibliographical research and individual semi-structured interviews, which allow for a targeted interview with focus, but also with a certain flexibility. In the analysis and interpretation of data, the content analysis technique was used, characterized by three moments: pre-analysis, content exploration and treatment of results. The study contributes to improving scientific knowledge on the researched subject, through a contingency view, focusing on the ideal management style, and a significant impact on organizational performance in educational organizations.